POKOK-POKOK PEMIKIRAN PENDIDIKAN HUKUM DI INDONESIA DALAM MEMENUHI KEBUTUHAN MASYARAKAT - Najmudin, Nandang (Syiar Hukum, 2011)
Thought prospective on legal education is directed to be capable of fulfilling communityâs needs, either those related to legal professions or those beyond them. Besides, it can be accomplished by some measures, among others : possesses basic capacities and academic knowledge on law globally, possesses skills required in guiding legal professions, possesses capacities in interdisciplinary sciences particularly those that support self-sufficiency at work, possesses professional ethic and responsibility, and possesses capacity in both thinking ways and life attitudes with a thinking pattern that ends at a principle of âDivine Words guide sciences and knowledge enlightens divine words. From legal aspect, legal education has provides a thought basis toward self-sufficient working. Therefore, legal the education taught should be relevant to the reality in community.